Addressing students' conceptions of diffusion and osmosis using conceptual change discussion protocol - Caballes, Dennis G. (Animo Repository, 2009)
This study intends to describe students understanding of certain fundamental biological concepts such as diffusion and osmosis and to assess the persistence of familiar misconceptions within 2 weeks of instruction. Written tests and the use of conceptual change discussion protocol were conducted to carry out this objective. A total of 1 intact class (n=50) of freshmen nursing students from Manila Doctors College (MDC) enrolled in Anatomy and Physiology Lecture course were the subjects of the study. To identify alternative conceptions of the learners and their view towards the course, a researcher-designed 18-item Diffusion and Osmosis Test (D & OT) and the Views About Science Survey (VASS Biology) were utilized. Prior to instruction, D & OT was administered as a pretest, and the same concept test was given as a posttest in an effort to determine the extent of their conceptual understanding. An individual interview and mental model construction were likewise conducted to the extreme scorers on D & OT to identify further both scientific and alternative conceptions. Results revealed that majority of the students increased their conceptual understanding on diffusion and osmosis reflective of the mean score gain in the posttest after the conceptual change discussion. Moreover, it was also apparent that even after instruction, alternative conceptions on the key areas under influence of life forces and concentration and tonicity were prevalent as noted in the decrease percentage of the students who got the correct answer in the D & OT and also from the culled responses during the interview and mental model construction activities given to the extreme scorers. An increased mean score in the D & OT seem to suggest that the Interactive Engagement technique employed such as CCDP could hold promise as effective pedagogy for concept change.